Leucismo en Astroblepus ubidiai (Pellegrin 1931; Astroblepidae: Siluriformes), de la provincia de Imbabura, Ecuador (2016)
The leucismo is an aberration in pigmentation, resulting from a genetic abnormality and occurs in all vertebrate groups in which the fish are included. In Ecuador, it has not reported such anomalies in fish. Is presented for the first time a case of partial leucismo in an individual of Andean Catfish (Astroblepidae), observed in a spring located near the Lake San Pablo Canton Otavalo, Imbabura Province, Ecuador.